Multi-Faceted Aspects of Reconstruction in Korean Scrambling - Park, Myung-Kwan (Lanaguage Research, 2021)
This paper investigates reconstruction in Korean long-distance scrambling. Saito (1989) argues that in long-distance scrambling, a wh-phrase is undone or radically reconstructed to its underlying position. In this paper, adapting Keine and Poole's (2018) analysis for the reconstruction of long-distance scrambled universal noun phrases (NPs) and indefinite NPs in Hindi-Urdu, we use Binding Condition (C) as a probe to test the validity of Saito's (ibid.) thesis regarding the reconstruction of such NPs as well as wh-phrases in Korean. We show that both universal quantificational phrases and wh-phrases in Korean have their quantificational and wh-licensing element/features reconstructed, with the rest of the parts staying in their surface positions and thus being outside the scope of Condition (C). On the contrary, all the indefinite NPs in the language at issue can optionally undergo radical/total reconstruction, thus interacting with Condition (C).